Histological differentiation of metastatic renal carcinoma in the cerebellum from cerebellar haemangioblastoma in von Hippel-Lindau's disease. - Clelland, C A (1989)
Two cases of von Hippel-Lindau's disease with special reference to the occurrence of renal carcinoma are presented. The first case demonstrates the difficulty of differentiating cerebellar haemangioblastoma from metastatic renal carcinoma affecting the cerebellum. The valuable differentiating histological features were positive staining of metastatic renal carcinoma by antiepithelial membrane antigen (anti-EMA) and the demonstration of a distinct pattern of packeting of cells by staining reticulin fibres. Staining with periodic acid Schiff and cytokeratin antibody (anti-CK) were not found to be useful. The second case exhibits the wide variety of neoplasms which may be present in von Hippel-Lindau's disease. Special stains support the findings of the first case.